Thermoluminescence of single wall carbon nanotubes synthesized by hydrogen-arc-discharge method. (March 2019) - Ortiz-Morales, A.; Ortiz-López, J.; Leal-Acevedo, B.; Gómez-Aguilar, R.
Abstract: Single Wall Carbon Nanotubes (SWNT) synthesized by the hydrogen-arc-discharge method were tested as thermoluminescent (TL) material and found to be highly resistant to gamma radiation. Gamma irradiation of the as-prepared material with doses between 1 and 20 kGy induced changes on the morphology of the SWNT, such as nanoloops, as observed by Scanning Electron Microscopy. From X-ray diffraction, the as-prepared material shows content of various forms of carbon, including nanotubes, hexagonal carbon (graphite), and rhombohedral carbon too. The full width at half maximum (FWHM) of diffraction peaks remain practically unchanged after irradiation. The glow curves show a single TL peak centered at about 449 K. Because the complex structure of the glow curves, it seems that the TL signal could be produced by a trap distribution instead of a single level of traps. To dilucidate the mechanism responsible of glow curves and the value of activation energy of traps, kinetic parameters like E eff, Δ E, and s of experimental the glow curves have been analyzed using computerized glow curve deconvolution (CGCD) considering a continuous distribution of trapping levels, peak shape and initial rise methods, as well as heuristic equations. The measured TL dosimetric properties may be summarized as follows: (a) moderate reproducibility of the TL signal (coefficient of variation 24.87%); (b) main peak activation energy of 1.206 eV; (c) threshold dose of ~1 kGy; (d) TL-sensitivity of ~7.0 × 10 −4 ; (e) human bone equivalence, i.e., high-Z material, Zeff = 15 and, (f) wide linear range of TL dose-response in the range 0.170–2.5 kGy. Highlights: Single Wall Carbon Nanotubes (SWNT) as potential material for use as detector phosphor for gamma radiation. Gamma irradiation of SWNT induced changes on the morphology of the SWNT. The Thermoluminescent (TL) properties of SWNT synthesized by the hydrogen arc plasma jet method reveals like sensitive and dose-resistant material.